A simple 90° Hybrid Branchline Coupler with Wideband Phase Balance for 5G Applications - Ünal, Ümit Can; Karaçuha, Kamil; İmeci, Sehabeddin Taha (Sciendo, 2024)
A 90° hybrid coupler operating at a central frequency of 5.40 GHz is introduced, offering high-performance characteristics with compact dimensions of 616.65 mm² (33.3 mm × 18.5 mm). These features are achieved while maintaining a design that makes it easy to produce. The unique aspect of this microstrip FR4 substrate-based design is the consistent S-parameters, which remain steady despite changes in structural dimensions, thereby making it adaptable to fabrication variations. The reported S-parameters measured in 5.4 GHz are as follows: |S11|= –29.46 dB, |S21|= –4.11 dB, |S31|= –3.96 dB, and |S41|= –21.23 dB. This hybrid coupler operates over a bandwidth of 0.8 GHz (16%), demonstrating remarkable performance within this spectrum. In addition to its design, the coupler exhibits robust resilience against changes in substrate parameters and structural dimensions, ensuring reliability during the fabrication process. Following thorough simulation studies, a physical prototype of the coupler was constructed and subjected to laboratory measurements. The experimental results align closely with the simulation data, validating the accuracy and predictability of the design. In comparison with other studies and designs documented in the literature, this compact, high-performance 90° hybrid coupler exhibits clear advantages in terms of size, isolation, phase deviation, and structural complexity. Therefore, the benefits and applicability of this presented structure in the context of microwave circuits and systems are underscored. It's noteworthy to mention that the central frequency of 5.4 GHz falls within the sub-6 GHz 5G band range.
Keywords: Fabrication Tolerance; Hybrid Coupler; Microwave Circuits; Microstrip Design; S-parameters